CIVIL LIABILITY OF HOSPITALS FOR MEDICAL RISKS LEGAL REVIEW AND IMPLICATIONS FOR MEDICAL PRACTICE INDONESIA - Pirma Ivan Ricky Manurung; Henry Aspan; Muhammad Arif Sahlepi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study adopts a normative legal perspective to explore the configuration and extent of civil liability attributed to hospitals in Indonesia, with particular attention to patient losses arising from alleged medical negligence or malpractice. Employing a doctrinal approach grounded in the examination of statutory provisions and legal doctrines, the research identifies a notable evolution in the allocation of responsibility. Legal accountability, which was previously directed toward individual healthcare professionals, has progressively shifted to hospitals as institutional entities. Notably, the Hospital Law, as stipulated in Article 46 of Law Number 44 of 2009, assigns hospitals a central role as the entities responsible for legal consequences arising from healthcare services. This legislative orientation reflects the principle of vicarious liability as articulated in Article 1367 paragraph (3) of the Indonesian Civil Code, under which an institution may be held legally responsible for acts committed by individuals operating within its sphere of authority . Within this legal construct, hospitals are regarded as autonomous legal persons responsible for the conduct of all healthcare personnel operating within their organizational framework, including physicians, and are consequently obliged to provide compensation when patients incur harm. The analysis also highlights the necessity of drawing a clear distinction between acts of professional negligence that give rise to civil liability and medical risks that are inherently associated with clinical interventions and have been duly acknowledged through valid informed consent. Taken as a whole, the findings indicate that Indonesian law has developed a structured and stringent model of hospital accountability, serving not merely as a means of providing remedies to patients, but also operating as a regulatory instrument means to improve healthcare quality and strengthen clinical risk management, thereby ensuring substantive legal protection for patients..